Dielectric reorientation and electrohydrodynamic instabilities in dichroic-dye-doped dual-cell liquid crystal smart window. Issue 1 (2nd January 2022) - Zhou, Bojun; Che, Chuncheng; Li, Yue; Wang, Chunlei; Wu, Yifan; Chang, Wenbo; Xiao, Yuelei; Cao, Xue; Lin, Gong; Song, Xuechao; Zhou, Yi
ABSTRACT: The paper demonstrates a dual-cell smart window based on dichroic-dyed-doped liquid crystal that is switchable among transparent, dark and scattering states. The dual-cell forms the crossed-polariser structure so very low transmittance is achieved. To characterise the concentration of ions in cells, voltage holding ratios with and without doping the dyes are measured. Polarisation optical microscopy (POM) of single cell that shows the transition from Freedericksz regime to turbulent state is also shown. In addition, the polarised and non-polarised voltage-transmittance and haze characteristics of the cells are measured. The increase in transmittance of dual cell after Freedericksz regime is explained and verified by simulations. By identifying the voltage when transmittance first increases as the threshold voltage of triggering electrohydrodynamic instabilities (EHDIs), its dependence on temperature, waveform, amplitude and frequency of driving voltage is investigated. Graphical abstract: uf0001